2013
DOI: 10.1016/j.neuroimage.2013.01.049
|View full text |Cite
|
Sign up to set email alerts
|

EEG correlates of time-varying BOLD functional connectivity

Abstract: Recent resting-state fMRI studies have shown that the apparent functional connectivity (FC) between brain regions may undergo changes on time-scales of seconds to minutes, the basis and importance of which are largely unknown. Here, we examine the electrophysiological correlates of within-scan FC variations during a condition of eyes-closed rest. A sliding window analysis of simultaneous EEG-fMRI data was performed to examine whether temporal variations in coupling between three major networks (default mode; D… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

16
277
1
1

Year Published

2013
2013
2017
2017

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 317 publications
(295 citation statements)
references
References 73 publications
16
277
1
1
Order By: Relevance
“…Finally, it is important to note that while fluctuations of dynFC might be driven by true non-stationarities and interactions of the time series, the origin of these signals could be both neurological and nonneurological. Ongoing and future research should further validate to what extent these origins can be disentangled (Chang et al, 2013); e.g., using concurrent measurements such as electroencephalography (EEG) and non-neurophysiological signals. …”
Section: Resultsmentioning
confidence: 99%
“…Finally, it is important to note that while fluctuations of dynFC might be driven by true non-stationarities and interactions of the time series, the origin of these signals could be both neurological and nonneurological. Ongoing and future research should further validate to what extent these origins can be disentangled (Chang et al, 2013); e.g., using concurrent measurements such as electroencephalography (EEG) and non-neurophysiological signals. …”
Section: Resultsmentioning
confidence: 99%
“…Brain activity during task-free fMRI experiments does not remain in a stationary resting state (33,34). It has been established that spontaneous fluctuations in intrinsic FC are not simply noise (35) and can be correlated with physiological markers, such as EEG or MEG power at different frequency bands (19,20), as well as with heart rate variability (21). Shifts in EEG power in the α-and θ-bands correspond to changes in arousal (36)(37)(38).…”
Section: Discussionmentioning
confidence: 99%
“…The association between BOLD signal fluctuation in the default mode network (DMN) and mind-wandering episodes (15)(16)(17) has prompted investigations into the behavioral correlates of spontaneous resting-state FC fluctuations (11,18). Although these fluctuations in FC have been shown to correlate with several physiological markers, such as electroencephalogram (EEG) power, magnetoencephalography (MEG) power, and heart rate variability (19)(20)(21), their behavioral significance remains unclear.…”
mentioning
confidence: 99%
“…Chang et al (2013b) recently linked heart rate variability to dynamic FC in regions associated with vigilance and arousal, suggesting the contribution of autonomic factors to the observed nonstationarity. Chang and colleagues also showed that alpha band power in EEG was related to FC fluctuations between the DMN and the dorsal attention network (Chang et al, 2013a). Further concurrent EEG-fMRI studies will be crucial in clarifying the relationship between these fluctuations and neural dynamics, as well as how they relate to attentional states.…”
Section: Timescales and Potential Confounds Of Dynamic Fcmentioning
confidence: 97%